(untitled) (Quinto Sol, 2017)
This article considers the transformations of the concept “totalitarianism” in Argentina liberal-conservative thought, and its main implications. Firstly, some parts of the international post-war liberal debate are summarized in order to emphasize a broadened interpretation of totalitarian phenomena that not only includes Nazi-fascist and Communist regimes, but also points to the totalitarian traits of Democracy itself. Secondly, it is shown that Argentina’s liberal-conservative intellectuals incorporated this notion of totalitarianism through two moves: they highlighted the totalitarian attributes of Argentine Democracy as it was practiced by majoritarian political parties, and they presented a binary conception of Democracy, according to which there would be a true and desirable Democracy (liberal, moderate and respectful of civil rights) and a false and execrable Democracy (populist, excessive, and potentially totalitarian). For liberal-conservative intellectuals of Argentina, the return of Peronism by elections was like a phantom that threatened the true democracy, a democracy which should be defended of this intimate totalitarian enemy.